Skin-Related Adverse Reactions Induced by Oral Antidiabetic Drugs-A Review of Literature and Case Reports - Justyna Kowalska; Dorota Wrześniok (MDPI AG, 2024)
Type 2 diabetes (T2DM) is a chronic metabolic disease with a steadily increasing prevalence worldwide. Diabetes affects the function of many organs, including the skin. Pharmacotherapy for T2DM is mainly based on oral hypoglycemic drugs. The therapeutic strategy is chosen taking into account the individual patient's characteristics, among other comorbidities. Antidiabetic drugs can induce cutaneous adverse reactions (CADRs) ranging in severity from mild erythema to serious disorders such as DRESS or Stevens-Johnson syndrome. CADRs can result from hypersensitivity to the drug but can also be related to the mechanism of action of the drug or cross-reactivity with drugs of similar structure. This paper reviews CADRs induced by oral antidiabetic drugs, considering their dermatological manifestations and possible pathomechanisms. Particular attention was paid to specific dermatological conditions such as dipeptidylpeptidase 4 inhibitor-associated bullous pemphigoid or Fournier's gangrene associated with sodium-glucose cotransporter 2 inhibitor therapy. Knowledge of the dermatological manifestations of CADRs is important in clinical practice. Recognition of a skin lesion resulting from an adverse drug reaction allows for appropriate management, which in this case is primarily related to drug discontinuation. This is particularly important in the treatment of T2DM since this disease has a high prevalence in the elderly, who are at higher risk of adverse drug reactions.